Modified mandated choice for organ procurement. Issue 3 (1st June 2003) - Chouhan, P; Draper, H
Abstract : Presumed consent to organ donation looks increasingly unlikely to be a palatable option for increasing organ procurement in the UK following the publication of the report into events at Alder Hey and elsewhere. Yet, given that the alternative to increasing the number of cadaveric organs available is either to accept a greater number of live donations, or accept that people will continue to die for the want of an organ, public policy makers remain obliged to consider other means of increasing the procurement rate. In this paper, we meet the main objections to mandated choice (namely that it undermines autonomy and that mandated donation is preferable). We have modified the traditional approach to mandated choice to take into account the force of the objection that mandated donation is preferable, by accepting that people can and do make bad decisions about organ donation and proposing that all accompanying public education and information about cadaveric donation should be directed in favour of donation.